REWAS 2013 Enabling Materials Resource Sustainability - Kvithyld, Anne.; Meskers, Christina; Kirchain, Randolph; Krumdick, Greg.; Mishra, Brajendra; Reuter, Markus; Wang, Cong.; Schlesinger, Mark.; Gaustad, Gabrielle; Lados, Diana; Spangenberger, Jeffrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume compiles topics from the REWAS 2013 symposium at the TMS Annual Meeting, focusing on different aspects of sustainability. It discusses how to realize sustainability in such areas as transportation, the built environment, electrical and electronic equipment and infrastructure, energy production, and water systems. Enabling sustainability topics include the use of metals and materials processing, recycling and recovery, as well as process design and modeling. The book focuses on understanding sustainability through life cycle management and analysis, systems modeling and design, and education and consumer awareness.
Keywords: Materials -- Analysis; Refuse and refuse disposal; Materials; Characterization and Analytical Technique; Waste Management/Waste Technology; Materials Engineering